Soprano, Germán y Tato, María Inés (Dirs.) (2022). Malvinas y las guerras del siglo XX. Buenos Aires: Teseo Press, 292 pp. - Noguera, Roberto Manuel (2023)
Reseña de Soprano, Germán y Tato, María Inés (Dirs.) (2022). Malvinas y las guerras del siglo XX. Buenos Aires: Teseo Press, 292 pp.